Impacts of spatio-temporal variability in forest Landscape metrics on soil quality, erosion severity and patch morphology in the Copperbelt Province of Zambia - Cho, Moses Azong (University of Pretoria, 2022)
Thesis (PhD (Forest Science))--University of Pretoria, 2021.